Estimates of global bilateral migration flows by gender between 1960 and 2010 - Guy J. Abel (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
Measures of international migration flows are often limited in both availability and comparability. This paper aims to address these issues at a global level using an indirect method to estimate country to country migration flows from more readily available bilateral stock data. Estimates are obtained over five and ten-year periods between 1960 and 2010 by gender, providing a comprehensive picture of past migration patterns. The estimated total amount of global international migrant flows is shown to generally increase over the 50 year time frame. The intensity of migration flows over five and ten-year periods fluctuate at around 0.6 and 1.25 percent of the global population respectively, with a noticeable spike during the 1990-95 period. Gender imbalances in the estimated flows between selected regions were found to exist, such as recent movements into oil rich Gulf States from South Asia. The sensitivity of flow estimates to alternative input stock and demographic data as well as changes in political geography are explored.
Keywords: 300; International migration; migration estimation; migration flows; migration stocks; global migration